2008
DOI: 10.1021/ja8022169
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Assembly of Highly Potent Analogues of Bryostatin 1 via Pyran Annulation: Bryostatin Look-Alikes That Mimic Phorbol Ester Function

Abstract: Highly potent bryostatin analogues which contain the complete bryostatin core structure have been synthesized using a pyran annulation approach as a key strategic element. The A ring pyran was assembled using a pyran annulation reaction between a C1-C8 hydroxy allylsilane and an aldehyde comprising C9-C13. This pyran was transformed to a new hydroxy allylsilane and then coupled with a preformed C ring aldehyde subunit in a second pyran annulation, with concomitant formation of the B ring. This tricyclic interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
81
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 19 publications
3
81
0
2
Order By: Relevance
“…2011;11(11): 1370- 92 The final version of record is available at http://www.eurekaselect.com/88010/article DOI: 10.2174/156802611795589584 11 was proven correct by the corresponding pivaloyloxy (analogue 17) and methylene (analogue 18) derivatives, which showed better binding affinities (Ki of 6.6 and 5.3 nM, respectively) compared to compound 14. Furthermore, the Blumberg group showed that the removal of the methyl and hydroxyl groups in ring A of bryostatin 1 gave compounds that retained excellent binding to PKCα (0.7-3.0 nM, compounds 21-24) but that evoked phorbol-like tumor promoting responses [50,51]. Alternatively, compound 11, which has the same C7-C9 substituents as bryostatin 1 and lacks only the C30 methoxy carbonyl group, showed a Ki value of 0.52 nM for PKCα but is also a functional antagonist of PMA (8) [52].…”
Section: Structure-activity Studiesmentioning
confidence: 99%
“…2011;11(11): 1370- 92 The final version of record is available at http://www.eurekaselect.com/88010/article DOI: 10.2174/156802611795589584 11 was proven correct by the corresponding pivaloyloxy (analogue 17) and methylene (analogue 18) derivatives, which showed better binding affinities (Ki of 6.6 and 5.3 nM, respectively) compared to compound 14. Furthermore, the Blumberg group showed that the removal of the methyl and hydroxyl groups in ring A of bryostatin 1 gave compounds that retained excellent binding to PKCα (0.7-3.0 nM, compounds 21-24) but that evoked phorbol-like tumor promoting responses [50,51]. Alternatively, compound 11, which has the same C7-C9 substituents as bryostatin 1 and lacks only the C30 methoxy carbonyl group, showed a Ki value of 0.52 nM for PKCα but is also a functional antagonist of PMA (8) [52].…”
Section: Structure-activity Studiesmentioning
confidence: 99%
“…4). [53][54][55] They found that 3 exhibited greater affinity for PKCa than did bryo-1. They also tested the function of 3 using U937 leukemia cells.…”
Section: Challenges To the Development Of Anticancer Drugs Kmentioning
confidence: 99%
“…This compound possesses excellent affinity for PKC (K i ¼ 3 nM), is orders of magnitude more potent than bryostatin against several human cancer cell lines, and can be synthesized in a step-economical fashion (29 total steps) scalable to meet clinical demand. Recent work by Keck and coworkers has provided further examples of the effectiveness of this design strategy (55)(56)(57)(58).…”
mentioning
confidence: 99%